Development of Inquiry-Based E-Poster Media on Natural Science Learning Digestive System Material in Elementary Schools - Rahmi, Miftah; Nari, Nola (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the validity and practicality of inquiry-based media development on digestive system-based material in grade 5 elementary school students. The type of research used is development research using a 4-D model (define, design, develop, and disseminate). The research instrument used validation sheets, practicality sheets. While the results were analyzed with descriptive techniques. The results of this study indicate that students' learning motivation increases by using inquiry-based e-poster learning media. This can be seen in the results of the validation test of the e-poster media of the inquiry-based digestive system that was developed which is very valid and the results of the practicality test through a response questionnaire are categorized as very practical. Thus the e-poster media inquiry-based that was developed is valid and practical to use as a means of conveying digestive system material to 5th grade students in elementary schools.